Antibody responses induced by Trichobilharzia regenti antigens in murine and human hosts exhibiting cercarial dermatitis - Lichtenbergová, Lucie; Kolbeková, Petra; Kouřilová, P; Kašný, Martin; Mikeš, Libor; Haas, Hans; Schramm, Gottfried; Horák, Petr; Kolářová, Libuše; Mountford, A. P (Parasite immunology, 2008)
Cercariae of bird schistosomes (genus Trichobilharzia) are able to penetrate the skin of mammals (noncompatible hosts), including humans, and cause a Th2-associated inflammatory cutaneous reaction termed cercarial dermatitis. The present study measured the antibody reactivity and antigen specificity of sera obtained after experimental infection of mice and natural infection of humans. Sera from mice re-infected with T. regenti showed a bias towards the development of antigen-specific IgM and IgG1 antibodies and elevated levels of total serum IgE, indicative of a Th2 polarized immune response. We also demonstrate that cercariae are a source of antigens triggering IL-4 release from basophils collected from healthy human volunteers. Analysis of sera from patients with a history of cercarial dermatitis revealed elevated levels of cercarial-specific IgG, particularly for samples collected from adults (> 14 years old) compared with children (8-14 years old), although elevated levels of antigen-specific IgE were not detected. In terms of antigen recognition, IgG and IgE antibodies in the sera of both mice and humans preferentially bound an antigen of 34 kDa. The 34 kDa molecule was present in both homogenate of cercariae, as well as cercarial excretory/secretory products, and we speculate it may represent a major immunogen initiating the Th2-immune response associated with cercarial dermatitis.
Keywords: Antibodies, Helminth; financování organizované; dospělí; Animals; dítě; Antigens, Helminth; Age Factors; imunoglobulin G; interleukin-4; Adult; Dermatitis; Adolescent; imunoglobulin M; věkové faktory; lidé; protilátky helmintové; Mice; Schistosomatidae; Immunoglobulin E; myši; Immunoglobulin G; Financing, Organized; Interleukin-4; antigeny helmintové; molekulová hmotnost; Immunoglobulin M; bazofily; Basophils; imunoglobulin E; dermatitida; Child; zvířata; Molecular Weight; mladiství; Humans